Application of Snowmelt Runoff Model in Sind catchment of Kashmir Himalaya - Shafiq, Mifta ul; Bhat, Irshad Ahmad; Singh, Harmeet; Bhat, Mohd Shafi; Ahmed, Pervez (National Geographical Journal of India, 2022)
Mountainous regions of the world act as the reservoirs of water due to their enormous snow and glacier resources. Quantification of snow and glacier melt runoff is important for water resource management in the downstream areas. The present study applies Snowmelt Runoff Model (SRM) to estimate the streamflow for Sind catchment in Kashmir Himalayas. In-situ daily temperature and precipitation data along with Moderate Resolution Imaging Spectrometer (MODIS) derived Snow Cover Area (SCA) were used to calibrate and validate the model. Digital Elevation Model (DEM) was used to prepare the area elevation curve of the Sind catchment. Several model parameters for streamflow were optimized during the calibration period (2011 - 2013) which were validated during 2014 - 2015. The accuracy of the model using coefficient of determination (R2) varied from 0.76 during calibration and 0.87 during validation period. The percentage difference in the volume (Dv) during the study period was around 3%. The results depict the relative capability of SRM to estimate the streamflow though more accurate estimation of model parameters can increase the model simulation results